A Novel Nitrite Reductase from Acinetobacter haemolyticus for Efficient Degradation of Nitrite - Xiao-Yan Yin; Emmanuel Mintah Bonku; Jian-Feng Yuan; Zhong-Hua Yang (Biomolecules, 2025)
Nitrite reductases play a crucial role in the nitrogen cycle, demonstrating significant potential for applications in the food industry and environmental remediation, particularly for nitrite degradation and detection. In this study, we identified a novel nitrite reductase (AhNiR) from a newly isolated denitrifying bacterium, Acinetobacter haemolyticus YD01. We constructed a heterologous expression system using E. coli BL21/pET28a-AhNir, which exhibited remarkable nitrite reductase enzyme activity of 29 U/mL in the culture broth, substantially higher than that reported for other strains. Structural analysis of AhNiR revealed the presence of [Fe-S] clusters, with molecular docking studies identifying Tyr-282 and Ala-289 as key catalytic sites. The enzymatic properties of AhNiR demonstrated an optimal pH of 7.5 and an optimal catalytic temperature of 30 °C. Its kinetic parameters, Km and vmax, were 1.53 mmol/L and 10.18 mmol/min, respectively, fitting with the Michaelis–Menten equation. This study represents the first report of a nitrite reductase from a denitrifying bacterium, providing a new enzyme source for nitrite degradation applications in the food industry and environmental remediation, as well as for biosensing technologies aimed at nitrite detection.